3D Printing of Photocatalytic Filters Using a Biopolymer to Immobilize TiO2 Nanoparticles. Issue 5 (27th February 2019) - Sangiorgi, A.; Gonzalez, Z.; Ferrandez-Montero, A.; Yus, J.; Sanchez-Herencia, A. J.; Galassi, C.; Sanson, A.; Ferrari, B.
Abstract : Titanium oxide-based photocatalytic filters were produced by Fused Deposition Modelling (FDM) using biopolymers obtained from renewable biomass resources. The thermoplastic route allows shaping composites through the immobilization of photoactive TiO2 nanoparticles in an environmentally friendly bioplastic such as the polylactic acid (PLA). Composites with an inorganic charge of 30 wt% of TiO2 nanoparticles (NPs) exhibit a 100% methyl orange (MO) degradation after 24 h of light exposition due to the extremely uniform dispersion of the nanophase within the polymer matrix in the FDM feedstock. Surface modification of TiO2 NPs allows the optimization of the colloidal dispersion and stabilization of the inorganic charge in a PLA solution and hence, the optimal distribution of nano-photoactive points in the TiO2 /PLA filaments and scaffolds. The proposed new route of processing improves the dispersion of nano-charges comparing with the traditional thermo-pressing routes used for mixing thermoplastics based composites, avoiding the thermal degradation of the polymer and providing a customised product. In this manuscript the evolution of photodegradation with the increase of TiO2 content in the composite and the variation of the filter geometry was evaluated.